Strategi Personal Selling, Pemasaran Getok Tular dan Pemasaran Media Sosial terhadap Keputusan Pembelian dengan Brand Awareness Sebagai Variabel Moderasi - Isha Milani; Hery Margono (Jurnal Akuntansi dan Pajak, 2023)
The This study aims to empirically examine the influence of personal selling on purchasing decisions, the influence of verbal communication on purchasing decisions, the influence of social media on purchasing decisions, the influence of personal selling, verbal communication and social media moderated by brand awareness on purchasing decisions. This analysis uses independent variables, namely personal selling, getuk tular, and social media. The dependent variable is the purchase decision, while the moderating variable is brand awareness. The sample was carried out by purposive sampling method. Data was collected by using questionnaires distributed directly to 100 respondents. The statistical method uses moderated regression analysis, by testing the t statistic test hypothesis. The results of this study indicate that the effect of personal selling on purchasing decisions, the influence of word of mouth on purchasing decisions, the influence of social media on purchasing decisions, the influence of personal selling, social media, and social media moderated by brand awareness on purchasing decisions have significant results and have a direct influence on the dependent variable.